Properties of Cavities in Biological Structures—A Survey of the Protein Data Bank - Chwastyk, Mateusz; Panek, Ewa A.; Malinowski, Jan; Jaskólski, Mariusz; Cieplak, Marek (Frontiers in Molecular Biosciences, 2020)
We performed a PDB-wide survey of proteins to assess their cavity content, using the SPACEBALL algorithm to calculate the cavity volumes. In addition, we determined the hydropathy character of the cavities. We demonstrate that the cavities of most proteins are hydrophilic, but smaller proteins tend to have cavities with hydrophobic walls. We propose criteria for distinguishing between cavities and pockets, and single out proteins with the largest cavities.